2013
DOI: 10.1002/adv.21389
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polythiophene/Sb2O3 Nanocomposite Using Sodium Dodecylbenzenesulfonate for the Removal of Pb (ІІ)

Abstract: Polythiophene-dodecylbenzenesulfonate/antimon oxide nanocomposite was synthesized via in situ chemical oxidative polymerization method at room temperature in aqueous media, and its capability for the removal of lead ions from aqueous solution was studied. Product was characterized by Fourier transfer infrared spectroscopy, X-ray diffraction, and scanning electron microscopy. The results indicate that the Sb 2 O 3 and dodecylbenzenesulfonate influence the properties of products. Batch studied were done to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 47 publications
0
5
1
Order By: Relevance
“…Although the adsorption ability of the PTh‐Cu nanocomposite prepared in the present study is lower than that reported in the previous works, 24,25,44 this study gives a critical point on the creation of adsorbents with polymeric surfactants. On the other hands, the preparation and modification of the composites are simply performed at mild reaction conditions.…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…Although the adsorption ability of the PTh‐Cu nanocomposite prepared in the present study is lower than that reported in the previous works, 24,25,44 this study gives a critical point on the creation of adsorbents with polymeric surfactants. On the other hands, the preparation and modification of the composites are simply performed at mild reaction conditions.…”
Section: Resultscontrasting
confidence: 72%
“…Through the combination of two counterparts at the nanoscale, the resulted composites not only keep the inherent properties but also often show higher processability, more stable stability, and even interesting improvements caused through the interaction of nanoparticle–matrix. In the case of polymer/inorganic nanoparticles composites, the incorporated nanoparticles are easy to separate from the adsorption system without the potential release into the environment, but still maintaining unique inherent physical and chemical properties 22–25 . The polymer matrix has proved to be ideal support for the fabrication of composites as adsorbents considering the adjustable surface functionality and the excellent mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…4 Conductive polymers (CPs), such as polypyrrole (PPy), polyaniline (PAni) and polythiophene (PTh), have attracted considerable attention due to their unique properties such as ease of synthesis, high stability under ambient conditions and variable conductivity. [5][6][7] In particular, CPs contain heteroatom, e.g., N atom in PAni and PPy and S atom in PTh, which plays a significant role in toxic metal ion elimination from an aqueous solution by chelation. 7,[8][9][10][11][12][13][14][15][16] On the other hand, ease of operation is also a very essential property for an ideal adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In particular, CPs contain heteroatom, e.g., N atom in PAni and PPy and S atom in PTh, which plays a significant role in toxic metal ion elimination from an aqueous solution by chelation. 7,[8][9][10][11][12][13][14][15][16] On the other hand, ease of operation is also a very essential property for an ideal adsorbent. Magnetic separation, in comparison with other techniques, such as precipitation, centrifugation and filtration, has revealed facile operation and reduced capital costs.…”
Section: Introductionmentioning
confidence: 99%
“…2 Therefore, effective removal of Pb 2+ from waste water is great importance and necessity to environmental sustainability. Some methods, such as chemical precipitation, 3,4 chemical reduction, 5 reverse osmosis, 6 float membrane filtration 7 and adsorption [8][9][10] are widely used in removing and recovering Pb 2+ from waste water. But the low selective separation is still a very large shortcoming using these methods.…”
mentioning
confidence: 99%